2020
DOI: 10.1029/2020jc016140
|View full text |Cite
|
Sign up to set email alerts
|

Residual Sediment Transport in Tidally Energetic Estuarine Channels With Lateral Bathymetric Variation

Abstract: The residual sediment transport in tidally energetic estuarine channels is investigated by means of idealized cross-sectional modeling. The lateral bathymetric variation follows a Gaussian profile, assuming longitudinal uniformity. The total along-channel residual sediment flux is decomposed into contributions from an advective flux and a tidal pumping flux. Two important mechanisms are found to modify the tidal covariance between sediment concentration and current velocity, thereby contributing to the tidal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Detailed physical investigations of this phenomenon have shown that either flood-dominance or ebb-dominance along estuary channels can be explained by the relationship between tidal flow asymmetry (local shear stress differences) and the cross-sectional channel geometry (morphology). Comprehensive treatments of this phenomenon can, for example, be found in Dronkers (1986Dronkers ( , 2005, Friedrichs and Aubrey 1988;Friedrichs (1995), Wang et al (1999), Prandle (2009), and Zhou and Stacey (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed physical investigations of this phenomenon have shown that either flood-dominance or ebb-dominance along estuary channels can be explained by the relationship between tidal flow asymmetry (local shear stress differences) and the cross-sectional channel geometry (morphology). Comprehensive treatments of this phenomenon can, for example, be found in Dronkers (1986Dronkers ( , 2005, Friedrichs and Aubrey 1988;Friedrichs (1995), Wang et al (1999), Prandle (2009), and Zhou and Stacey (2020).…”
Section: Discussionmentioning
confidence: 99%